Challenging the status quo: gender norms in Croatian juvenile correctional settings - Matković, Elizabeta; Borić, Ivana; Ćosić, Andrea; Sočo, Anamarija (Frontiers in Sociology, 2024)
Gender norms and issues related to gender are highly relevant when it comes to treatment of juveniles in correctional institutions, especially related to their risky behavior and personal characteristics (such as personality traits, intellectual capability, culture, ethnicity etc.). Furthermore, many juveniles in correctional institutions are exposed to violence and are also perpetrators of violent criminal acts. This paper will give an overview of national policies related to gender-sensitive treatment in Croatia as a background to research aimed to describe the reflection of gender issues and gender norms in practical work with juveniles in Croatian correctional institutions. The research is based on qualitative approach and includes focus groups with youth workers from various organizations who implemented programs for youth in correctional institutions. Preliminary results show that gender and gender norms are not specifically targeted in treatment programs within the institutions. The initiative to implement gender issues mainly comes from organizations from the civil sector through different workshops. Juveniles express relatively rigid gender norms that are supported by rigid organization of correctional institutions especially for males. This research shows the importance of clearer focus to gender-sensitive programing and gender sensitive treatment programs that will strongly be integrated in everyday practice of correctional institutions. The precondition for this is largely connected to deconstructing stereotypes about gender and gender norms both for youth and professionals working with them.